Testing a physical education-delivered autonomy supportive intervention to promote leisure-time physical activity in lower secondary school students: the PETALS trial - Jekaterina Schneider; Juho Polet; Mary Hassandra; Taru Lintunen; Arto Laukkanen; Nelli Hankonen; Mirja Hirvensalo; Tuija H. Tammelin; Timo Törmäkangas; Martin S. Hagger (BMC, 2020)
Abstract Background Inadequate physical activity in young people is associated with several physical and mental health concerns. Physical education (PE) is a potentially viable existing network for promoting physical activity in this population. However, little research has been conducted on whether PE teachers can influence students' engagement in leisure-time physical activity. The present study therefore examined the efficacy of an intervention aimed at increasing PE teachers' autonomy support on students' leisure-time physical activity (the PETALS trial). The intervention was guided by the trans-contextual model (TCM) explaining the processes by which PE teachers' provision of autonomy support during PE promotes students' motivation and engagement in physical activity in their leisure time. Methods The study adopted a cluster-randomized, waitlist control intervention design with randomization by school. Participants were PE teachers (N = 29, 44.83%female; M age = 42.83, SD = 9.53 yrs) and their lower secondary school students (N = 502, 43.82%female; M age = 14.52, SD = 0.71 yrs). We measured TCM constructs, including perceived autonomy support, autonomous motivation in PE and leisure time, beliefs and intentions towards leisure-time physical activity, and physical activity behavior at baseline, post-intervention, and at one-, three-, and six-months. Study hypotheses were tested through a series of ANOVAs and structural equation models using post-intervention and one-month follow-up data. Results We found no changes in TCM constructs or physical activity behavior in either group at post-intervention or at 1 month. Path analyses supported two propositions of the TCM as change variables: perceived autonomy support had a significant effect on autonomous motivation in PE and autonomous motivation in PE had a significant effect on autonomous motivation in leisure time. Although we found a direct effect of autonomous motivation in leisure time on physical activity, we did not find support for the third premise of the TCM that autonomous motivation in leisure time indirectly affects physical activity through beliefs and intentions. Conclusions Current findings did not support the efficacy of the PETALS intervention at changing physical activity behavior and TCM constructs. More research is required to determine whether the TCM predictive validity is supported when other model variables are manipulated through experimental and intervention studies. Trial registration ISRCTN, ISRCTN39374060 . Registered 19 July 2018. Prospectively registered.